Implementation of the Use of Village Funds in Improving Welfare Communities in Jailolo District, West Halmahera Regency, Province North Maluku - SAMSUDDIN, Ardian; RUSANDRY, Rusandry (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose: This research aims to determine, implement, and use the village budget to improve the community's welfare in the Jailolo sub-district, West Halmahera Regency. Therefore, planning for the implementation and accountability of the Village Government is needed. Oversight by the West Halmahera Regency Government plays a vital role in improving community welfare through the village budget.Methodology: This research uses qualitative methods, interviews with the Village Government of the Jailolo District, and directly with the community. This research also limits research to choosing which data are relevant and which are irrelevant.Findings: The results of this study indicate that administratively the management of the Village Government is very effective in the planning, implementation, and accountability of ADD. There are still many things that need to be evaluated by the Jailolo Village Government in terms of improving community welfare through the village budget. Especially in terms of reporting, the village government consistently reports village funds to the village head every month.Implication:The government of West Halmahera Regency aims to enhance the management of village funds by implementing better supervision. It will involve obtaining reports from the Village Head, who is responsible for the funds. The objective is to ensure that village development aligns with the RPJMD and RKPD, creating a unified system in the development area.